The patient experience of sleep problems and their treatment in the context of current delusions and hallucinations. (18th August 2015) - Waite, Felicity; Evans, Nicole; Myers, Elissa; Startup, Helen; Lister, Rachel; Harvey, Allison G.; Freeman, Daniel
Abstract : Objectives: There is increasing recognition that sleep problems are common in patients with psychosis, that they exacerbate delusions and hallucinations and should be a treatment target. The aim of this study was to gain a patient perspective on the nature of sleep problems in psychosis and experience of treatment. Design: A qualitative, semi‐structured interview‐based study to explore patient accounts of sleep problems and associated psychological treatment. Methods: Ten patients with recent delusions and hallucinations, who had experienced sleep problems and received psychological treatment during a clinical trial (the Better Sleep Trial), were interviewed. Responses were analysed using interpretative phenomenological analysis. Results: Patients reported experiencing problems of getting to sleep, staying asleep, too much sleep, nightmares, and erratic sleep patterns. These sleep problems caused emotional distress, fatigue, and reduction in daytime activities. Worry and psychotic experiences disturbed sleep, while consequent tiredness meant that patients coped poorly with voices and persecutory fears. Treatment for sleep problems was viewed very positively and considered to have wide‐ranging impacts. Conclusions: Sleep disturbance is a major problem for patients with psychosis, which should be treated more often in services using evidence‐based interventions. Practitioner points: Psychological interventions for sleep problems are valued by patients with psychosis. Patients with current distressing psychotic experiences report wide‐ranging benefits from a brief psychological intervention for sleep problems.